Respuesta :
Answer:
The solution of the equation is 3.3 and (-0.3).
Step-by-step explanation:
We need to find the exact solution of the given quadratic equation [tex]x^2-3x-1=0[/tex].
If the quadratic equation is in the form of [tex]ax^2+bx+c=0[/tex], then the solution of this equation is given by :
[tex]x=\dfrac{-b\pm \sqrt{b^2-4ac} }{2a}[/tex]
On comparing the given equation with this above, it means, a = 1, b = -3 and c = -1.
So,
[tex]x=\dfrac{-(-3)\pm \sqrt{(-3)^2-4\times 1\times (-1)} }{2\times 1}\\\\x=\dfrac{-(-3)+\sqrt{(-3)^{2}-4\times1\times(-1)}}{2\times1}, \dfrac{-(-3)-\sqrt{(-3)^{2}-4\times1\times(-1)}}{2\times1}\\\\x=3.3, -0.30[/tex]
So, the solution of the equation is 3.3 and (-0.3).